Evaluasi Kinerja Perawat Pelaksana di Rawat Inap dengan Pendekatan Personal Balance Score Card - Tjiawi, Midoro; Ginting, Chrismis Novalinda; Nasution, Ali Napiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate the performance of nurses with the Personal Balance Scorecard approach. The research method uses a cross-sectional study. The results of the study are that there is an effect of the use of a personal balanced scorecard on the quality of performance with a p-value of 0.003, there is an effect of the use of a personal balanced scorecard on work standards with a p-value of 0.021, there is an effect of the use of a personal balanced scorecard on customer perception with a p-value of 0.027, and there is an effect of the use of a personal balanced scorecard on learning and development with a p-value of 0.030. In conclusion, there is a significant effect of the use of a personal balanced scorecard on the quality of performance, work standards, customer perception, and learning and development of adult inpatient nurse performance at Sapta Medika Indrapura Hospital. Keywords: Evaluation, Performance, Personal Balance Score Card